ORGANIC AGRICULTURE AND RURAL PARTICIPATION AT THE SOUTHERN COAST OF JALISCO UNIVERSITY CENTER, UNIVERSITY OF GUADALAJARA, MEXICO - Villalvazo López, Víctor Manuel (2022)
This article analyzes the role that rural agriculture workshops play in designing strategies for dialogue promotion, empowerment and rural popular education, from 2010 to 2019, at the Southern Coast of Jalisco University Center (cucsur in Spanish) of the University of Guadalajara. The methodological approach is qualitative, with contributions from participatory research. The techniques used are the realization of theoretical and practical workshops, where the country people “learn by doing”. The workshops proved to be adequate spaces not only to generate appropriate agricultural technologies, but to build communication and education alternatives.